Akselerasi Pemulihan Ekonomi Masyarakat Pasca Bencana Melalui Inovasi Pakan Ikan Mandiri Berbasis Buah Campnosperma auriculatum Desa Lancat - Sianipar, Herna Febrianty; Sianturi, Tambos; Siahaan, Theresia Monika; Sijabat, Apriani; Sinaga, Christa Voni Roulina; Simanjuntak, Bernard (Abdimas Mandalika, 2026)
Abstract: The natural disaster in Lancat Village caused significant damage to fisheries infrastructure and crippled the economy of local fish farmers due to the high cost of commercial feed. This community service program aims to accelerate economic recovery through innovative, independent fish feed based on the use of Campnosperma auriculatum (Terentang) fruit as an alternative raw material. The implementation method consisted of four main stages: outreach and data collection on damaged facilities, technical training on feed formulation, intensive production assistance, and economic performance evaluation. The results of the activity showed an increase in the community's technical skills in feed nutritional formulation from 10% to 80%. The use of this innovative feed significantly reduced variable production costs by 40% and increased farmer profit margins per harvest cycle. The success of this program not only restored post-disaster production capacity but also created a sustainable, circular economic model based on local resources. The transformation of the community from feed consumers to independent producers is a key factor in strengthening the economic resilience of Lancat Village against market fluctuations and future disaster risks.Abstrak: Bencana alam di Desa Lancat telah menyebabkan kerusakan infrastruktur perikanan yang signifikan dan melumpuhkan ekonomi pembudidaya ikan lokal akibat tingginya biaya pakan komersial. Kegiatan pengabdian masyarakat ini bertujuan untuk mengakselerasi pemulihan ekonomi melalui inovasi pakan ikan mandiri berbasis pemanfaatan buah Campnosperma auriculatum (Terentang) sebagai bahan baku alternatif. Metode pelaksanaan dilakukan melalui empat tahapan utama: sosialisasi dan pendataan kerusakan sarana, pelatihan teknis formulasi pakan, pendampingan intensif produksi, serta evaluasi performa ekonomi. Hasil kegiatan menunjukkan peningkatan keterampilan teknis masyarakat dalam formulasi nutrisi pakan dari 10% menjadi 80%. Penggunaan pakan inovasi ini secara nyata mampu menekan biaya variabel produksi sebesar 40% dan meningkatkan margin keuntungan pembudidaya per siklus panen. Keberhasilan program ini tidak hanya memulihkan kapasitas produksi pasca bencana, tetapi juga menciptakan model ekonomi sirkular berbasis sumber daya lokal yang berkelanjutan. Transformasi masyarakat dari konsumen pakan menjadi produsen mandiri menjadi kunci utama dalam memperkuat ketahanan ekonomi Desa Lancat terhadap fluktuasi pasar dan risiko bencana di masa depan.